From Manual to Digital: An Innovation in The Performance Appraisal System of Medan City Government Employees - Kiki Farida Ferine; Rikha Murliasari; Arif Saefudin; Fahruddin Fahruddin (Cita Konsultindo Research Center, 2024)
This research aims to focus on analysing how website-based SKP in Medan City to form Smart ASN is carried out. The method used is a qualitative method with a case study approach. The data collection techniques include in-depth interviews, direct observation or observation, and documentation. Researchers used interactive model analysis as an analysis technique in this study. Data analysis begins with reviewing all available data from various sources. After reviewing, the next step is data reduction, unit arrangement, categorisation, and data interpretation. Data presentation was done with narrative text and pictures. The last stage is conclusion drawing or verification, where researchers express conclusions from the data obtained during the data collection. The results showed that the Medan City Government had encouraged organisational success through professional ASN HR performance management. One method is a measurable employee performance appraisal system using a website-based online SKP management system. The Medan City Government's working mechanism follows the Agile work scale concept. ASN core values become a strong foundation for strengthening work culture and become a guide in implementing ASN performance management to support the implementation of e-government towards Smart ASN. Smart ASN is a digital talent and leader supporting bureaucratic transformation in Indonesia. On the other hand, there are weaknesses when giving assessments to ASN by other ASN colleagues that are often not realised, namely the existence of a culture of reluctance in giving assessments. As a recommendation, coordination with the central government can overcome the overlapping management systems implemented to make it easier for ASNs to achieve their performance targets